2010
DOI: 10.1111/j.1468-3083.2010.03836.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis infection in psoriatic patients on anti‐TNF therapy: report of a case series with 144 patients

Abstract: This is the first study to underscore the incidence of LTBI in patients with psoriasis treated with anti-TNF therapy in the Spanish population. We support that the use of TST is still reliable and an effective diagnostic method for the detection of LTBI in anti-TNF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 18 publications
1
28
2
Order By: Relevance
“…25,26 LTBI was diagnosed by TST in 13Á4% of patients with rheumatic diseases (rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis) undergoing treatment with infliximab in Spain. 27 The clinical implications of diagnosing LTBI are very important.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 LTBI was diagnosed by TST in 13Á4% of patients with rheumatic diseases (rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis) undergoing treatment with infliximab in Spain. 27 The clinical implications of diagnosing LTBI are very important.…”
Section: Discussionmentioning
confidence: 99%
“…Latent tuberculosis infection reactivation is of special concern with the use of tumour necrosis factor inhibitors [31], and the risk seems to be higher with monoclonal antibodies than with etanercept in patients with rheumatoid arthritis [32,33]. In our study, 8 patients showed a positive reaction only after a second TST procedure, indicating that a 2-step TST may be helpful for the detection of latent tuberculosis prior to a course of biological therapy in certain patient populations [21] despite negative results of TST and/or γ-interferon release assays.…”
Section: Discussionmentioning
confidence: 98%
“…Before treatment, a chest X-ray and a tuberculin skin test (TST) with protein-purified derivative were performed to rule out latent tuberculosis. In patients with negative TST results, the TST was repeated to rule out false-negative results due to potential immunosuppression [21]. Follow-up data (physical examination, vital signs and laboratory tests, disease activity, observed AEs, and concomitant used drugs) were collected every 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Recent epidemiological studies reported a prevalence rate of LTBI in patients with psoriasis of 5-22% in Italy, 11-14 10% in London, 28 11% in Taiwan 29 and 20-29% in Spain, which is a highprevalence country for tuberculosis. 30,31 LTBI was diagnosed using TST in 13Á4% of patients with rheumatic diseases (RA, ankylosing spondylitis and PsA) undergoing treatment with infliximab in Spain. 32 The present study showed some fluctuations of QFT-GIT results between baseline and follow-up at month 31 AE 1Á7.…”
Section: Discussionmentioning
confidence: 99%